Care bundles for women during pregnancy, labor/birth, and postpartum: a scoping review protocol - Ryan, Theo (My University, 2022)
Objective: This scoping review will identify the existence and type of care bundles developed, evaluated, or used by health care professionals in providing maternity care to women during pregnancy, labor/birth, and postpartum. Introduction: Care bundles consist of at least 3 to 5 evidence-based health care interventions that are implemented together in 1 clinical episode, consistently. Care bundle use is predicated on the notion that better clinical outcomes can be achieved when the interventions, often existing as part of standard care, are used collectively rather than in isolation. Although widely adopted in some health care sectors (eg, in critical care), care bundle use during pregnancy, labor/birth, and postpartum appears relatively recent. Inclusion criteria: This review will include records on women during pregnancy, labor/birth, and postpartum (up to 6 weeks) as recipients of care bundles applied by a health care professional. Women may be at low or high risk of maternity complications, receiving maternity care in hospital, community, or home settings, in any geographical location. Care bundles applicable to neonates will be excluded. Methods: The Maternity and Infant Care, MEDLINE, CINAHL, Embase, and Epistemonikos databases will be searched from 2000 onward. The concepts of “care bundles” AND “maternity care” will underpin the search strings. Language limitations will not be applied, although only records published in English will be included. Two reviewers will independently assess the records for inclusion and extract the data. The findings will be charted using narrative summary text, illustrative tables, and illustrative figures. Scoping review registration: Open Science Framework https://osf.io/bdwfy/
PUBLISHED
Keywords: care bundles; health care intervention; maternal health; maternity care; scoping review; Maternity Care; Midwifery